Penerapan Metode Multi Objective Optimization on the Basis of Ratio Analysis (MOORA) Dalam Pemilihan Mekanik Terbaik Sepeda Motor - Ahmad Sofian Sinaga; Fauriatun Helmiah; Chitra Latiffani (Forum Kerjasama Pendidikan Tinggi, 2022)
A mechanic is a person in charge of checking, maintaining, repairing, replacing spare parts according to the analysis of the Service Advisor (the person who serves and receives every customer or customer complaint) listed in the workshop work order, with reference to the standardization of work that has been set and most mechanics specialize in in certain areas such as auto mechanics, bicycle mechanics, motorcycle mechanics, boiler mechanics, general mechanics, air conditioning and freezing, aircraft mechanics, diesel engine mechanics. One of the existing methods in a decision support system is the MOORA (Multi-Objective Optimization On The Basis Of Ratio Analysis) method. The reason the author chose the MOORA method is because this method is very simple, stable, and powerful, even this method does not require an expert in mathematics to use it and requires simple mathematical calculations. In previous research, it is known that there is no selection of the best mechanic at company. With the use criteria used are troubleshooting (analyzing problems and repairing vehicles), years of service, attendance and letters of reprimand. With these criteria, it is expected to produce the best motorcycle mechanic decisions